Research and application of new fast self-healing technology of distribution network based on line topology and beat frequency attenuation - Wei Wang; Kai Zhang; Shixuan Lv; Zhihong Zheng; Guanliang Li; Lu Bai (Results in Engineering)
The distribution network is frequently susceptible to various faults due to its complex structure and dynamic operating environment. Traditional fault-handling methods primarily rely on manual inspections and relay protection devices, which often result in prolonged power supply restoration times and low self-healing recovery rates, failing to meet the high-reliability demands of modern power systems. To address these challenges, this paper proposes a novel fast self-healing technology for distribution networks based on line topology and beat frequency attenuation. The node identification is uniformly defined, and the electrical topology of the distribution network is represented using an equivalent topology diagram, enabling the construction of a multi-objective optimization model for network reconfiguration. The characteristics of low-frequency natural vibration components are analyzed, and a positive-sequence component control strategy is employed to regulate the output current of inverter-interfaced distributed generation (IIDG). Additionally, a redundant resource network structure model is developed to facilitate rapid power restoration for outage-affected loads. The proposed method is validated using the IEEE 33-node distribution network, which comprises 33 nodes and 37 switch-equipped branches. The reference voltage is set to 12.66 kV, with a three-phase power reference value of 10 MVA. The total load under the current operating condition is 5084.26 + j2547.32 kVA. The experimental results demonstrate that the proposed approach achieves a minimum node voltage of 12.16 kV, a time delay within 3 ms, a self-healing recovery rate exceeding 90 %, a reduced network loss of 122.7 kW, and an improved minimum node voltage of 0.9477 pu.